SUCCESS-HPON A next-generation optical access architecture for smooth migration from TDM-PON to WDM-PON. - An, Fu-Tai (IEEE Communications magazine)
Optical access networks are considered to be a definite solution to the problem of upgrading current congested access networks to ones capable of delivering future broadband integrated services. However, the high deployment and maintenance cost of traditional point-to-point architectures is a major economic barrier. Current TDM-PON architectures are economically feasible, but bandwidth-limited. In this article we first discuss the possible role of WDM in access networks and investigate the associated issues. We then present the Stanford University Access Hybrid WDM/TDM Passive Optical Network (SUCCESS-HPON), a next-generation hybrid WDM/TDM optical access architecture that focuses on providing a smooth migration path from current TDM-PONs to future WDM-PONs. The first testbed for this architecture is described, along with the experimental results obtained, including feasibility of bidirectional transmission on the same wavelength on the same fiber for access networks and ONU modulation of upstream data on continuous waves provided by the OLT, eliminating the need for tunable components at the ONUs. The development of a second testbed and the issues it will address, including the implementability of the SUCCESS-HPON MAC protocol and scheduling algorithms, are also described.